Mapping of epidemiological determinants of confirmed COVID-19 cases among health-care workers of municipal corporation of Delhi: A roadmap to risk reduction - Sunil Kumar Singh; Sumit Jethani; Anshumali Gupta; Bhushan Dattatray Kamble; Saudan Singh; Pooja Ahlawat (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Coronavirus disease (COVID-19) is a respiratory illness caused by a novel coronavirus which can spread from person to person. Health-care workers of any medical college and hospital are at more risk to the coronavirus disease (COVID-19) than the general population. The aim of this study was to assess the epidemiological profile of confirmed COVID-19 cases among health-care workers of Municipal Corporation of Delhi. METHODOLOGY: A cross-sectional study was planned among 422 health-care workers of Municipal Corporation of Delhi. The questionnaire consisted of questions about sociodemographic data, personal history, and clinical profile such as signs and symptoms and their duration. Data were analyzed by SPSS software version 21.0, and, Chi-square test and logistic regression were used. RESULTS: Mean age of study subjects was 41.1 ± 9.8 years, and males (57.6%) were more as compared to (42.4%) females. Out of total participants, about one-third (36.4%) of study participants were asymptomatic. Study participants with higher education status adjusted odds ratio (AOR) 2.43 (1.25-4.70), living in overcrowding AOR 3.74 (1.86-7.54), and having some comorbidity AOR 2.78 (1.57-4.92) were at higher risk of being symptomatic. CONCLUSION: This study concludes that about one-third of study participants were asymptomatic. Factors such as higher education status, living in overcrowding, presence of some comorbidity, and smokeless tobacco consumption were significantly associated with symptomatic COVID-19 cases. Hence, there is a need to identify these risk factors at an early stage in order to design prevention strategies for better control of such pandemics in future.